(untitled) (mathematica didactica, 2023)
Using the example of an optimization problem (isoperimetric problem), the article shows the didactic possibilities offered by the discussion of different solutions and variations of the problem. Thus, the article pleads for a mathematical education, which lets mathematics be experienced as an open discipline, which opens up the subject matter by multiple approaches, opens up space for own ideas and thus counteracts a one-dimensional teaching-learning concept.